ETIOLOGY, CLINICAL MANIFESTATIONS, TREATMENT AND PREVENTION OF TICK-BORNE ENCEPHALITIS - A. G. Gaivoronskaya; M. G. Galitskaya; L. S. Namazova-Baranova (Union of pediatricians of Russia, 2013)
At present, tick-borne encephalitis is registered in Siberia, Far East, Urals, Belarus and central regions of Russia. The viral infection has also been recently revealed among the population of the previously problem free regions: Penza, Yaroslavl, Magadan, Kamchatka, Moscow and Ivanovo. The disease manifests itself in various forms: febrile, meningeal, meningoencephalitic etc. The disease prognosis is favorable in case of a meningeal or febrile form, but significantly worse in case of a meningoencephalitic form - fatal outcomes take place in 25-30% of cases. Residuals in the form of convulsive hyperkinetic syndrome may remain in some patients even if the treatment started in time. Active immunization is the primary tick-borne encephalitis prevention.